Efectos del estrés postraumático sobre la neurobiología y el funcionamiento neuropsicológico de mujeres víctimas de violencia sexual: una revisión sistemática (2023)
By establishing the link between sexual violence and psychological factors, the mediating effect of post-traumatic stress disorder on cognitive deficit and macrostructural atrophy of the nervous system of female victims is recognized. In order to broaden this panorama, the objective of this review is to analyze the available scientific evidence about the effects of post-traumatic stress on the neurobiology and neuropsychological functioning of women victims of sexual violence. To this end, electronic databases Pubmed, Scopus, Web of Science, and Science Direct were systematically searched for instrumental studies on cognitive processes and brain structures of women with a history of sexual violence diagnosed with posttraumatic stress disorder. The search strategy yielded a total of 1,302 studies, of which 37 went to full-text review and 9 met the eligibility criteria to be included in the review. The results indicate a significant effect of PTSD on the cognitive and neurobiological variables evaluated, so that the victims experienced lower performance in tasks of verbal, visual and working memory, attention, interference and verbal IQ, as well as presented decreased gray matter volume in areas such as the amygdala, insula, bilateral lingual gyrus, and intracalcarine cortex.